Neurotropic Tick-Borne Flavivirus in Alpine Chamois (Rupicapra rupicapra rupicapra), Austria, 2017, Italy, 2023 - Norbert Nowotny; Maria Lucia Mandola; Isabella Monne; Zoltán Bagó; Chiara Nogarol; Alice Fusaro; Katharina Dimmel; Barbara Moroni; Lisa Guardone; Jolanta Kolodziejek; Elisa Palumbo; Gabriela Stanclova; et al. (Viruses)
The European subtype of tick-borne encephalitis virus (TBEV-Eur; species Orthoflavivirus encephalitidis, family Flaviviridae) was the only tick-borne flavivirus present in central Europe known to cause neurologic disease in humans and several animal species. Here, we report a tick-borne flavivirus isolated from Alpine chamois (Rupicapra rupicapra rupicapra) with encephalitis and attached ticks, present over a wide area in the Alps. Cases were detected in 2017 in Salzburg, Austria, and 2023 in Lombardy and Piedmont, Italy. The virus strains exhibit 94.8–97.3% nucleotide identities to each other and are more closely related to Louping ill viruses (LIV; Orthoflavivirus loupingi; 90–92% identities) than to TBEV-Eur (less than 88%). The chamois-derived virus strains, tentatively termed “Alpine chamois encephalitis virus”, form a well-supported independent genetic clade with Spanish goat encephalitis virus, clearly separated from other LIV. This supports its designation as a new virus subtype with the proposed shared taxonomic name “Spanish goat and Alpine chamois encephalitis virus subtype” within the species Orthoflavivirus loupingi. The zoonotic potential of this newly identified virus subtype as well as its host range in other animal species including farm animals needs to be further investigated.